CONCEPT AND CONTENT OF THE LEGAL STATUS OF A CONSUMER OF MEDICAL SERVICES - Стратонов, Василь Миколайович; Гавловська, Аліна Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2020)
Introduction. The mechanism of legal regulation of consumer protection in general, and consumer rights in the field of medical services in particular, has passed certain historical stages of formation and development. Of particular importance in the system of organizing consumer protection at the international level was the creation in 1960 of the International Organization of Consumers - Consumers International, which is a world federation of consumer groups. The activities of international and national organizations have a common goal of "consumer protection" by consolidating the efforts of consumer groups and relevant organizations and protecting their rights, including interests, before the relevant state and international bodies and organizations. Summary of the main research results. The legal status of the patient is a complex theoretical and legal phenomenon, including the legal personality of the patient, basic rights, duties, responsibilities, guarantees for the realization of his rights and freedoms, and the like. The content of the legal status of the patient consists of his rights, obligations and legal responsibility. Conclusions. The entire system of patients’ rights - consumers of medical services can be conditionally divided into the following groups: 1) general medical rights - this group of rights is enshrined in the basic regulatory legal acts. General health rights include: the right to health care; the right to consent to or refuse medical care; the right to information; the right to confidentiality and protection of personal data; 2) special medical rights; 3) the rights of persons who forcibly acquired the legal status of a patient; 4) the rights of persons who participate in medical and biological experiments and tests.